Ciclo de aprendizaje de KOLB y desarrollo del pensamiento crítico en estudiantes de bachillerato, Unidad Educativa Otavalo - Ruiz, Edwin J. (2022)
The purpose of this research was to determine the impact of Kolb's learning cycle (ERCA) regarding the development of higher cognitive skills of critical thinking among high school students of the Otavalo Educational Unit, in the year 2021. Critical thinking skills are considered a fundamental aim in the educational field, in order to teach critical thinking. In this context, Ecuador obtained a minimum score in the competencies of mathematics, reading and science, as a participant in the Program for International Student Assessment for Development (PISA-D), which took place in 2018. This research was developed using a mixed, exploratory, non-experimental, field-based approach. The applied instruments were a survey addressed to 44 teachers that allowed to identify the high implementation of Kolb's learning cycle-based learning (ERCA) sessions. In addition to that, the level of critical thinking development was determined through a sample of 267 students representing high school students. The diagnosed students mark of critical thinking development has been classified between a medium and a low level. It is important to strengthen the educational process with active methodologies such as project-based learning or inclusive classroom etc. However, the low level of critical thinking skills development among students may have been affected by the adaptation of teaching and learning sessions from face-to-face to the virtual session due to the pandemic caused by covid-19.